2017
DOI: 10.1177/0884533617724742
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Essential Amino Acids as a Predictor of Skeletal Muscle Depletion in Patients With Cachexia and Advanced Gastrointestinal Cancers

Abstract: Higher serum EAA/TAA ratio and CRP were associated with depletion in psoas muscle area, which led to a diagnosis of sarcopenia, in patients with advanced gastrointestinal cancers. These parameters at baseline could be predictors of cancer cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Thirdly, high serum CRP suggests increased Interleukine 6 production [44], which promotes muscle protein breakdown by several mechanisms including both inhibition of muscle protein synthesis, repair, contractility and function [45], and stimulation of the hypothalamus-pitituary-cortical axis leading to increased cortisol production. Lastly, high EAA/TAA and BCAA/TAA ratios observed in the study patients were previously reported in cancer individuals with cachexia [46,47].…”
Section: Discussionsupporting
confidence: 77%
“…Thirdly, high serum CRP suggests increased Interleukine 6 production [44], which promotes muscle protein breakdown by several mechanisms including both inhibition of muscle protein synthesis, repair, contractility and function [45], and stimulation of the hypothalamus-pitituary-cortical axis leading to increased cortisol production. Lastly, high EAA/TAA and BCAA/TAA ratios observed in the study patients were previously reported in cancer individuals with cachexia [46,47].…”
Section: Discussionsupporting
confidence: 77%
“…Our data showing elevated levels of protein turnover, myofibrillar protein breakdown and muscle wasting correspond with other metabolic studies in small groups of cancer patients [19,48,58] and therefore we think that our study provides useful information about protein metabolism in patients undergoing chemotherapy. We showed that even in patients who would not be classified as pre-cachectic or cachectic, the body responds to the disease and the treatment, resulting in a significantly higher protein turnover and myofibrillar protein breakdown and many deteriorations in the production and clearance rate of amino acids, which were related to muscle function, physical function and quality of life.…”
Section: Weight Loss Sarcopenia and Obesitysupporting
confidence: 90%
“…The finding of an increased muscle hypercatabolism in our patients was supported by the fact that they were found to be affected by sarcopenia. Moreover, increased contributions of EAAs and BCAAs to TAAs are similar to those detected in cachectic cancer patients, 34,35 in whom increased EAA and BCAA/TAA ratios are associated with a decrease in psoas muscle volume. 36 On the other hand, acidosis and cancer share an increased ubiquitin-proteasome proteolytic pathway.…”
Section: Dialysis Techniques and Aa Lossessupporting
confidence: 52%